Perbandingan Penerapan PPh Pasal 21 Sebelum dan Sesudah Pandemi COVID-19 - Burhanudin Yusuf; Risma Dwi Riyanti; Atira Hasya; Salsabilah Michel Efendi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to compare the implementation of Income Tax (Article 21) before and after the COVID-19 pandemic. The research uses a descriptive qualitative approach through a literature review of tax regulations, official reports from the Directorate General of Taxes, and academic journals. The results show that prior to the pandemic, Article 21 Income Tax was applied normally with the tax borne by employees. During the pandemic, the government provided tax incentives through the Article 21 Income Tax Borne by the Government (DTP) policy as part of a fiscal stimulus package. After the pandemic, the incentive policy was discontinued and the implementation returned to the normal tax system. This study concludes that fiscal policy is adaptive to crisis conditions, and tax incentives have proven effective in maintaining public purchasing power and encouraging tax compliance. Keywords: Income Tax, Article 21, COVID-19, Tax Incentives, Fiscal Policy.